Porous graphene negative electrode material and preparation method thereof
By using a reasonable ratio of graphene and carbon nanotubes and modifying with nitrogen-doped nano-metal particles, the problem of poor conductivity caused by stacking of graphene anode materials was solved, realizing the preparation of porous graphene anode materials with high capacity and high conductivity, which are suitable for industrial applications.
Patent Information
- Application Number
- CN202511527826.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2026-01-16
AI Technical Summary
Existing graphene anode materials have poor conductivity due to the stacking of layers, and the high-temperature preparation process is energy-intensive and causes serious environmental pollution, making it difficult to meet the requirements of high-capacity, high-current charging and discharging.
By rationally proportioning graphene and carbon nanotubes, carbon nanotubes are used as bridges and supports to connect dispersed graphene sheets. A conductive network is constructed through nitrogen doping and nano-metal particles, and a porous structure is built at low temperature using an in-situ oxidation-reduction method.
It significantly reduces electrode internal resistance, improves high-current charging and discharging capability, and increases electronic conductivity by 30%-50%. The process is simple and environmentally friendly, making it suitable for industrial production.
Smart Images

Figure CN121355231A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of graphene materials technology, and in particular to a porous graphene anode material and its preparation method. Background Technology
[0002] Lithium-ion batteries, as a novel energy storage device, are widely used in electric vehicles, portable electronic devices, and other fields due to their high energy density and long cycle life. The anode material, as a core component of lithium-ion batteries, directly affects the battery's electrochemical performance. Currently, commercially available anode materials are mainly graphite-based, but their theoretical specific capacity is relatively low, making it difficult to meet the application requirements of high-capacity, high-current charge-discharge. Graphene, with its excellent electronic conductivity, high specific surface area, and good mechanical properties, has become a research hotspot for lithium-ion battery anode materials.
[0003] However, the strong van der Waals forces between graphene sheets lead to tight stacking during preparation and subsequent drying and carbonization processes, resulting in a significant reduction in specific surface area, obstruction of electron conduction channels, and consequently, increased electrode internal resistance and decreased high-current charge-discharge performance. While existing technologies modify graphene by introducing carbon materials or metal particles, the interfacial bonding between carbon materials and graphene is weak, and metal particles tend to agglomerate, making it difficult to form a stable synergistic conductive network. Furthermore, most preparation processes require pore structure construction at temperatures above 800℃, which not only easily damages the crystal structure of graphene but also suffers from high energy consumption, cumbersome process steps, and severe environmental pollution, limiting its industrial application. Therefore, this invention proposes a porous graphene anode material and its preparation method to address the problems existing in the prior art. Summary of the Invention
[0004] To address the aforementioned problems, this invention proposes a porous graphene anode material and its preparation method. By rationally proportioning graphene and carbon nanotubes, the carbon nanotubes simultaneously act as bridges and supports, effectively connecting dispersed graphene sheets and suppressing their stacking. This forms a high-speed electron conduction channel that penetrates the material particles, significantly reducing the internal resistance of the electrode and greatly improving the high-current charging and discharging capability of the anode. This solves the problem of poor conductivity caused by stacking in traditional graphene anodes.
[0005] To achieve the objectives of this invention, the invention is implemented through the following technical solution: a porous graphene anode material comprising the following mass ratio components: 10-30 parts graphene, 2-8 parts carbon nanotubes, 5-15 parts nitrogen source, 1-5 parts nano-metal particles, 0.5-3 parts dispersant, and 50-80 parts solvent;
[0006] The carbon nanotubes are used to connect dispersed graphene sheets and suppress their stacking, the nitrogen source is used to introduce nitrogen-doped defect sites in the graphene carbon framework, and the nano-metal particles are used to construct a graphene-metal conductive network.
[0007] A further improvement is that the nano-metal particles are one or more of nickel particles, cobalt particles, and iron particles, with a particle size range of 20-100 nm.
[0008] A further improvement is that the nitrogen source is one or more of melamine, urea, and dicyandiamide; and the carbon nanotubes have a diameter of 5-20 nm and a length of 1-5 μm.
[0009] A further improvement is that the dispersant is one or more of polyvinylpyrrolidone, sodium dodecylbenzenesulfonate, and Tween-80; and the solvent is one or more of deionized water, ethanol, and N-methylpyrrolidone.
[0010] The further improvement lies in the fact that the graphene is a reduced product of graphene oxide with a reduction degree of ≥90% and a sheet diameter of 0.5-5μm.
[0011] A method for preparing a porous graphene anode material includes the following steps:
[0012] S1: Graphene, carbon nanotubes and dispersant are added to a solvent and mixed and dispersed to obtain a graphene-carbon nanotube mixed dispersion;
[0013] S2: Add a nitrogen source and nano-metal precursor to the mixed dispersion, and carry out an in-situ oxidation-reduction reaction at 50-80℃ to reduce the nano-metal precursor to nano-metal particles, thereby obtaining a reaction slurry containing nano-metal particles.
[0014] S3: The reaction slurry is subjected to low-temperature heat treatment to construct a porous structure at 200-400℃, and after cooling, a porous graphene anode material is obtained.
[0015] Further improvements are made in the following aspects: In S1, the mixing and dispersion method is ultrasonic dispersion, the ultrasonic power is 300-500W, and the ultrasonic time is 20-60min; in S2, the in-situ oxidation-reduction reaction temperature is 50-80℃, and the reaction time is 1-3h.
[0016] A further improvement is that, in S2, the nano-metal precursor is one or more of nickel nitrate, cobalt nitrate, and ferric chloride, and the ratio of its addition amount to the weight of the nano-metal particles is 1.5-3:1.
[0017] A further improvement is made in S3, where the heating rate of the low-temperature heat treatment is... The heat treatment process involves holding the material at a temperature of 1-3 hours and then cooling it to room temperature naturally. During this process, the nano-metal particles are further shaped and form a synergistic structure with nitrogen-doped graphene and carbon nanotubes.
[0018] A further improvement lies in the fact that the internal resistance of the porous graphene anode material after being fabricated into an electrode is calculated using the following formula:
[0019] ,
[0020] Where R is the internal resistance of the electrode, in ohms. ρ represents the resistivity of the porous graphene anode material, in ohms-cm. L is the thickness of the electrode, in centimeters (cm); S is the effective conductive area of the electrode, in square centimeters (cm²); k is the synergistic conductivity coefficient of carbon nanotubes and graphene, without dimensions, ranging from 0.85 to 0.98. The value of k increases linearly with the weight ratio of carbon nanotubes to graphene. When the weight ratio of carbon nanotubes to graphene is 0.1-0.4, the value of k corresponds to 0.85-0.98.
[0021] The beneficial effects of this invention are as follows:
[0022] 1. This invention achieves a reasonable ratio of graphene and carbon nanotubes, enabling carbon nanotubes to simultaneously act as bridges and supports, effectively connecting dispersed graphene sheets and inhibiting their stacking, forming a high-speed electron conduction channel that penetrates the material particles, significantly reducing the internal resistance of the electrode, greatly improving the high-current charging and discharging capability of the negative electrode, and solving the problem of poor conductivity caused by stacking in traditional graphene negative electrodes.
[0023] 2. This invention modifies the material by combining nitrogen doping with nano-metal particles. On the one hand, the pyrrole nitrogen and pyridine nitrogen generated by the decomposition of nitrogen source can be embedded in the graphene carbon skeleton, introducing a large number of defect sites, which increases the specific surface area of the material and provides more active centers for lithium ion adsorption. On the other hand, the nano-metal particles are uniformly dispersed between the graphene sheets, further inhibiting agglomeration and constructing a graphene-metal dual conductive network, which improves the electronic conductivity of the material by 30%-50%, achieving both high capacity and high conductivity.
[0024] 3. This invention uses an in-situ oxidation-reduction method to prepare the graphene crystal structure, which can be completed in just 3 steps. The pore structure is constructed at a low temperature of 200-400℃, which avoids high temperature damage to the graphene crystal structure, ensures the intrinsic properties of the material, and significantly reduces energy consumption and harmful gas emissions. The process is simple, green and environmentally friendly, and suitable for industrial mass production. Attached Figure Description
[0025] Figure 1 This is a flowchart of the present invention. Detailed Implementation
[0026] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0027] Example 1
[0028] according to Figure 1 As shown in the figure, this embodiment proposes a porous graphene anode material and its preparation method:
[0029] Material proportions
[0030] 20 parts graphene (reduction product of graphene oxide, reduction degree 92%, sheet diameter 2μm), 5 parts carbon nanotubes (diameter 10nm, length 3μm), 10 parts nitrogen source (melamine), 3 parts nano-metal particles (Ni particles, particle size 50nm), 1 part dispersant (polyvinylpyrrolidone, K30 type), and 61 parts solvent (deionized water).
[0031] Preparation steps
[0032] (1) Mixing and dispersing: 20 parts graphene, 5 parts carbon nanotubes and 1 part polyvinylpyrrolidone were added to 61 parts deionized water and ultrasonically dispersed for 30 minutes at 400W power and 20kHz frequency to obtain a uniform graphene-carbon nanotube mixed dispersion.
[0033] (2) In-situ reaction: Add 10 parts of melamine and 6 parts of nickel nitrate (nano metal precursor, weight ratio of 2:1 to Ni particles) to the dispersion, heat to 60°C, and stir magnetically at 500 rpm for 2 hours. During this period, nickel nitrate is reduced to Ni nanoparticles, and melamine is initially decomposed to obtain a reaction slurry containing nitrogen-doped precursor and Ni particles.
[0034] (3) Low temperature heat treatment: The reaction slurry was transferred to a tube furnace and heated to 300°C at 8°C / min. The porous structure was constructed under N2 protection (flow rate 50mL / min) for 2 hours. After natural cooling to room temperature, the porous graphene anode material was collected.
[0035] Performance verification
[0036] (1) Basic electrochemical performance:
[0037] Initial discharge specific capacity (1C rate, charge / discharge voltage 0.01-3V, tested with Blue Electric CT2001A): ;
[0038] Capacity retention after 100 cycles (under the same conditions as the previous cycle): 92%.
[0039] (2) Electrode internal resistance: calculated using the formula in claim 10. Actual AC impedance test value Error <2% (Test parameters: CHI660E workstation, frequency) (Amplitude 5mV)
[0040] (3) Key material parameters: material resistivity Four-probe test (25℃, 45% humidity): carbon nanotubes to graphene weight ratio 0.25, synergistic conductivity k=0.92.
[0041] Example 2
[0042] according to Figure 1 As shown in the figure, this embodiment proposes a porous graphene anode material and its preparation method:
[0043] Material proportions
[0044] 15 parts graphene (reduction degree 90%, sheet diameter 1μm), 3 parts carbon nanotubes (diameter 8nm, length 2μm), 8 parts nitrogen source (urea), 2 parts nano-metal particles (Co particles, particle size 30nm), 1.5 parts dispersant (sodium dodecylbenzenesulfonate), and 70.5 parts solvent (analytical grade ethanol).
[0045] Preparation steps
[0046] (1) Mixing and dispersing: 15 parts graphene, 3 parts carbon nanotubes and 1.5 parts sodium dodecylbenzenesulfonate were added to 70.5 parts ethanol and ultrasonically dispersed at 300W for 45min to obtain a mixed dispersion.
[0047] (2) In-situ reaction: Add 8 parts of urea and 3.6 parts of cobalt nitrate (weight ratio of 1.8:1 to Co particles), heat to 70℃ and stir for 1.5h. Cobalt nitrate is reduced to Co nanoparticles, and urea is decomposed to provide nitrogen source, thus obtaining reaction slurry;
[0048] (3) Low temperature heat treatment: The temperature is increased to 350℃ at 5℃ / min, and kept at the temperature for 2.5h under N2 atmosphere. After cooling, the porous graphene anode material is collected.
[0049] Performance verification
[0050] (1) Basic electrochemical performance:
[0051] Initial discharge specific capacity (1C rate): 1450mAh / g;
[0052] Capacity retention after 100 cycles: 90%.
[0053] (2) Electrode internal resistance: calculated by formula Actual AC impedance test value The error is <1.1%;
[0054] (3) Key material parameters: material resistivity The weight ratio of carbon nanotubes to graphene is 0.2, and the synergistic conductivity coefficient k=0.88.
[0055] Example 3
[0056] according to Figure 1 As shown in the figure, this embodiment proposes a porous graphene anode material and its preparation method:
[0057] Material proportions
[0058] 25 parts graphene (reduction degree 95%, sheet diameter 3μm), 6 parts carbon nanotubes (diameter 15nm, length 4μm), 12 parts nitrogen source (dicyandiamide), 4 parts nano-metal particles (Fe particles, particle size 80nm), 2 parts dispersant (Tween-80), and 51 parts solvent (analytical grade N-methylpyrrolidone).
[0059] Preparation steps
[0060] (1) Mixing and dispersing: 25 parts graphene, 6 parts carbon nanotubes and 2 parts Tween-80 were added to 51 parts N-methylpyrrolidone and ultrasonically dispersed at 500W for 20min to obtain a mixed dispersion.
[0061] (2) In-situ reaction: Add 12 parts of dicyandiamide and 10 parts of ferric chloride (weight ratio of Fe particles 2.5:1), heat to 50℃ and stir for 3h. Ferric chloride is reduced to Fe nanoparticles, and dicyandiamide is decomposed to introduce nitrogen doping, thus obtaining the reaction slurry.
[0062] (3) Low temperature heat treatment: The temperature is increased to 250℃ at 10℃ / min, and kept at the temperature for 1.5h under N2 atmosphere. After cooling, the porous graphene anode material is collected.
[0063] Performance verification
[0064] (1) Basic electrochemical performance:
[0065] First discharge specific capacity (1C rate): ;
[0066] Capacity retention after 100 cycles: 94%.
[0067] (2) Electrode internal resistance: calculated by formula Actual AC impedance test value The error is <1.3%;
[0068] (3) Key material parameters: material resistivity The weight ratio of carbon nanotubes to graphene is 0.24, and the synergistic conductivity coefficient k=0.95.
[0069] Verification data: Material resistivity was measured using an RTS-9 four-probe tester at an ambient temperature of 25℃ and humidity of 45%; AC impedance was measured using a CHI660E electrochemical workstation at a frequency range of 10⁻²-10⁻¹⁰.5 Hz, amplitude 5mV.
[0070]
[0071] This invention utilizes a rational ratio of graphene and carbon nanotubes, enabling the carbon nanotubes to simultaneously act as bridges and supports. This effectively connects dispersed graphene sheets and inhibits their stacking, forming a high-speed electron conduction channel that penetrates the material particles. This significantly reduces the internal resistance of the electrode and greatly enhances the high-current charge-discharge capability of the negative electrode, solving the problem of poor conductivity caused by stacking in traditional graphene negative electrodes. Furthermore, this invention employs nitrogen doping and composite modification with nano-metal particles. On one hand, the pyrrole nitrogen and pyridine nitrogen generated from the decomposition of the nitrogen source can be embedded into the graphene carbon framework, introducing numerous defect sites. This increases the specific surface area of the material and provides more active centers for lithium-ion adsorption. On the other hand, the uniform dispersion of nano-metal particles between the graphene sheets further inhibits aggregation and constructs a graphene-metal dual conductive network, improving the material's electronic conductivity by 30%-50%, achieving a balance between high capacity and high conductivity. Meanwhile, the present invention adopts an in-situ oxidation-reduction method for preparation, which can be completed in only 3 steps. Moreover, the pore structure is constructed at a low temperature of 200-400℃, which avoids high temperature damage to the graphene crystal structure, ensures the intrinsic properties of the material, and greatly reduces energy consumption and harmful gas emissions. The process is simple, green and environmentally friendly, and suitable for industrial mass production.
[0072] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A porous graphene negative electrode material, characterized in that, The graphene is 10-30 parts, the carbon nanotube is 2-8 parts, the nitrogen source is 5-15 parts, the nano metal particle is 1-5 parts, the dispersant is 0-3 parts, and the solvent is 50-80 parts. The carbon nanotube is used for connecting the dispersed graphene sheet and inhibiting the stacking thereof, the nitrogen source is used for introducing the nitrogen-doped defect site in the graphene carbon skeleton, and the nano metal particle is used for constructing the graphene-metal conductive network.
2. The porous graphene negative electrode material of claim 1, wherein: The nano metal particle is one or more of nickel particles, cobalt particles and iron particles, and the particle size range is 20-100 nm.
3. The porous graphene negative electrode material of claim 1, wherein: The nitrogen source is one or more of melamine, urea and dicyandiamide; the diameter of the carbon nanotube is 5-20 nm, and the length is 1-5 μm.
4. The porous graphene negative electrode material of claim 1, wherein: The dispersant is one or more of polyvinylpyrrolidone, sodium dodecylbenzenesulfonate and Tween-80; and the solvent is one or more of deionized water, ethanol and N-methylpyrrolidone.
5. The porous graphene negative electrode material of claim 1, wherein: The graphene is a reduction product of graphene oxide, the reduction degree is greater than or equal to 90%, and the sheet diameter is 0.5-5 μm.
6. A method for preparing a porous graphene negative electrode material, applied to the porous graphene negative electrode material in any one of claims 1-5, characterized in that, The method comprises the following steps: S1: adding graphene, carbon nanotube and dispersant into a solvent, and mixing and dispersing to obtain a graphene-carbon nanotube mixed dispersion liquid; S2: adding a nitrogen source and a nano metal precursor into the mixed dispersion liquid, and performing in-situ oxidation-reduction reaction at 50-80 DEG C to reduce the nano metal precursor into nano metal particles, so as to obtain a reaction slurry containing nano metal particles; S3: performing low-temperature heat treatment on the reaction slurry, constructing a pore structure at 200-400 DEG C, and obtaining a porous graphene negative electrode material after cooling.
7. The method of claim 6, wherein the method further comprises: In the S1, the mixing and dispersing mode is ultrasonic dispersion, the ultrasonic power is 300-500 W, and the ultrasonic time is 20-60 min; in the S2, the in-situ oxidation-reduction reaction temperature is 50-80 DEG C, and the reaction time is 1-3 h.
8. The method of claim 6, wherein the method further comprises: In the S2, the nano metal precursor is one or more of nickel nitrate, cobalt nitrate and ferric chloride, and the weight ratio of the addition amount of the nano metal precursor to the nano metal particle is 1.5-3:
1.
9. The method for preparing a porous graphene anode material according to claim 6, characterized in that: In the S3, the heating rate of the low-temperature heat treatment is 5-10 DEG C / min, the holding time is 1-3 h, the cooling mode is natural cooling to room temperature, and in the low-temperature heat treatment process, the nano metal particle is further shaped, and a synergistic structure is formed with the nitrogen-doped graphene and the carbon nanotube.
10. The method for preparing a porous graphene anode material according to claim 6, characterized in that: The internal resistance of the porous graphene negative electrode material after being made into an electrode is calculated by the following formula: , Wherein: R is the internal resistance of the electrode, in ohms ; p is the resistivity of the porous graphene negative electrode material, in ohm centimeter ; L is the thickness of the electrode, in centimeters (cm); S is the effective conductive area of the electrode, in square centimeters ; k is the synergistic conductive coefficient of carbon nanotube-graphene, unitless, with a value range of 0.85-0.98, the k value linearly increases with the weight ratio of carbon nanotube to graphene, when the weight ratio of carbon nanotube to graphene is 0.1-0.4, the k value corresponds to 0.85-0.98.